2022
DOI: 10.1186/s12967-022-03449-w
|View full text |Cite
|
Sign up to set email alerts
|

DLEU1 promotes cell survival by preventing DYNLL1 degradation in esophageal squamous cell carcinoma

Abstract: Background Emerging evidence has highlighted the critical roles of long noncoding RNAs (lncRNAs) in tumor development and progression. However, the biological functions and underlying mechanisms of DLEU1 in esophageal squamous cell carcinoma (ESCC) remain unclear. Methods LncRNA expression in ESCC tissues was explored using lncRNA microarray datasets. The functional roles of DLEU1 in ESCC were demonstrated by a series of in vitro and in vivo experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…DLEU1 stabilizes DYNLL1 by interfering with RNF114-mediated ubiquitination and proteasomal degradation of DYNLL1, subsequently upregulating the anti-apoptotic protein BCL2, thereby inhibiting cell apoptosis. This discovery not only reveals the significant biological function of DLEU1 in ESCC but also suggests that the DLEU1/DYNLL1 axis could be a promising target for ESCC treatment [42].Moreover, studies have found that DYNLL1 forms a complex with the mitochondrial cytochrome oxidase Cox4i1, crucial for clearing intracellular pathogens. The dissociation of the DYNLL1-Cox4i1 complex is key to releasing mitochondrial reactive oxygen species and regulating the intracellular proliferation of the bacterium Listeria monocytogenes.…”
Section: Discussionmentioning
confidence: 84%
“…DLEU1 stabilizes DYNLL1 by interfering with RNF114-mediated ubiquitination and proteasomal degradation of DYNLL1, subsequently upregulating the anti-apoptotic protein BCL2, thereby inhibiting cell apoptosis. This discovery not only reveals the significant biological function of DLEU1 in ESCC but also suggests that the DLEU1/DYNLL1 axis could be a promising target for ESCC treatment [42].Moreover, studies have found that DYNLL1 forms a complex with the mitochondrial cytochrome oxidase Cox4i1, crucial for clearing intracellular pathogens. The dissociation of the DYNLL1-Cox4i1 complex is key to releasing mitochondrial reactive oxygen species and regulating the intracellular proliferation of the bacterium Listeria monocytogenes.…”
Section: Discussionmentioning
confidence: 84%
“…This interaction promoted myeloid cell leukemia 1 (Mcl-1) splicing and facilitated Mcl-1L isoform switching, promoting proliferation, migration and invasion in TE-1 and KYSE170 cells, as well as inhibiting apoptosis ( 91 ). DLEU1 bound to dynein light chain LC8-type 1, inhibiting its ubiquitination and degradation by ring finger protein 114, thereby inhibiting apoptosis in KYSE410 and EC109 cells, promoting cisplatin/cis-diamminedichloroplatinum (CDDP) resistance and conferring resistance in CDX (KYSE410) cells ( 92 ). GK intronic transcript 1 bound to mitogen-activated protein kinase 1, preventing its interaction with dual specificity phosphatase 6 and activating the ERK/MAPK signaling pathway, promoting proliferation, invasion and migration in TE-1 and TE-10 cells, as well as being associated with clinical staging and prognosis ( 23 ).…”
Section: Lncrnas Upregulated In Esccmentioning
confidence: 99%